Pengembangan Aplikasi Pengadaan Barang Pada Koperasi Karyawan Dan Warga Al-Muslim Berbasis Web Dengan Metode SDLC - Andri Firmansyah; Tri Wahyuni (DPPM Universitas Pelita Bangsa, 2024)
The growth of information technology for entrepreneurs in Indonesia is very rapid, especially in the city of Bekasi. Al-Muslim Employees and Citizens Cooperative is one of the businesses engaged in cooperative sales of fulfillment needs within the Al-Muslim Foundation which has a large inventory of goods and needs better management. In carrying out its business processes, the Al-Muslim Employees and Citizens Cooperative has several problems including data processing is still manual by using records only so that it is vulnerable to lost or damaged data. Another problem is human error or people who process data from the process of recording incoming goods data, recording outgoing goods data, recording stock data. The method used in this research is Software Development Life Cycle (SDLC), this method describes the overall software development process to produce quality software and meet the expectations of system users. The result of this research is to build a procurement system to make it easier to control the amount of inventory of each item appropriately and can speed up the production of information on ordering goods so that there is no delay in ordering goods.